Design and thermal performance analysis of self-insulation concrete compound blocks - Xiao, Qidan; Deng, Hui; Gao, Bo; Zhao, Jun (Frontiers in Physics, 2024)
More than 60% of energy losses occur through the building envelope. Exterior wall insulation technology is widely used for wall insulation, but it is prone to cracking, falling off, and causing fires. Self-insulation concrete compound blocks (SIB) have attracted considerable attention in recent years for meeting building energy efficiency standards without the need for external insulation treatment. In this study, the shale ceramsite concrete (SCC) was prepared as the base material for the blocks through the orthogonal test and range analysis. In accordance with the insulation requirements of residential building walls, 12 types of self-insulation concrete compound blocks (SIB) were designed. The heat transfer process of these blocks was simulated and analyzed using Ansys Workbench, enabling a comparison of the thermal conductivity effects resulting from different hole distribution schemes in the insulation blocks. The simulated values were compared with the theoretical calculations, and the simulated results were in good agreement with the theoretical calculations. The results showed that TZ-12 exhibited the optimal hole configuration with a heat transfer coefficient of 0.5 W/(m2·K), which was 38.3% lower than that of the external insulation block TZ-9. Additionally, TZ-12 demonstrated the average compressive strength of 8.28 MPa and the minimum compressive strength of 7.45 MPa, meeting the requirements for MU7.5 strength grade and also satisfying the requirement of not less than MU5.0 when self-insulation blocks were used for external walls. The simulated heat flux rate of the self-insulation concrete compound block wall (SIBW) was 15.4 W, and its heat transfer coefficient was 0.56 W/(m2·K), which was 29.1% lower than that of the external thermal insulation wall (ETIW), meeting the design standard for achieving the 65% energy saving in residential buildings situated in regions with hot summers and cold winters.